Pengaruh Paritas Dan Usia Kehamilan Terhadap Kecemasan Pada Ibu Hamil di Puskesmas Jetis Kabupaten Ponorogo - Ambika Kurnia Mustikawati (Jurnal Delima Harapan, 2017)
Background: Pregnancy is a valuable thing, but also one of the great stresses for awoman both physically and mentally. Pregnant women with high anxiety will increase therisk of hypertension, difficulty sleeping and stroke, seizures and even death in the motherand fetus. At Puskesmas Kabupaten Ponorogo the number of pregnant women is 5903.Interview results, 21 out of 27 mothers say very anxious during pregnancy. The purposeof this study was to analyze the factors of parity and gestational age to anxiety inpregnant women.Subjects and Methods: The type of research is analytical with cross-sectional approach.Location of research at health center of Balong Kabupaten Ponorogo. Researchconducted on September 1 to October 15, 2016. Sample of 30 pregnant women usingproportional random sampling technique. Dependent variable is anxiety, while theindependent variable is parity and gestational age. Data collection techniques usingquestionnaires. Data analysis using Spearman's Rho using SPSS 18.0 for windowscomputer program.Results: The results showed that from 40 respondents, almost half were 13 (32.5%)multiparous had mild anxiety and nearly half were 13 (32.5%) primipara experiencedmoderate anxiety. of the 40 respondents, nearly half (12%) of 3 trimester pregnantwomen had moderate anxiety and a small proportion of 9 (22.5%) of 2 trimester pregnantwomen had mild anxiety. The result of calculation using spearman's rho statistic testobtained p = 0,006 <α 0,05 mean there is influence between parity with anxiety inpregnant woman with correlation coefficient of -0,424 which show intensity of influenceof medium that is if the smaller parity hence more anxiety level. The calculation ofgestational age with spearman's rho p = 0,023 <α 0.05 means that there is an influencebetween parity with anxiety in pregnant women with a correlation coefficient of 0.359which shows the weakness of weak influence.Conclusion: Different parity and gestational age affect anxiety levels in each pregnantwoman. It is hoped for research sites to provide a solution for pregnant women so as toreduce perceived anxiety and respondents are expected to have a good coping mechanismin the face of anxiety for his health and his fetus as well as preparation for labor.